The Education on Emergency Response and Disaster for Junior High School Students of Surakarta - Sjarifah, Ipop; Setyawan, Haris (Sebelas Maret University, 2016)
Emergency is abnormal and dangerous situations that threaten or require quick action to control, fixed and restored it to the safety condition. Most parts of Indonesia territory are vulnerable to disasters, whether natural and non-natural disasters or social disaster. Catastrophic incident may cause an emergency situation that must be carried out prevention and control into a safe condition, especially in the city of Surakarta that have strong possibilities to have floods, fires, earthquakes and volcanic eruptions. Geographically Surakarta located in watersheds of Bengawan Solo that potentially to face emergencies situation and disasters. Floods is possible to occur due to Surakarta is surrounded by more than three large reservoirs i.e. Waduk Gajah Mungkur, Waduk Cengklik, Waduk Delingan, Waduk Lalung and Waduk Kedungombo. Surakarta is also located near to Mount Merapi, which its eruption in 2013 had covered Yogyakarta and Surakarta .Junior High School (SMP) students are aged between 13-15 years who psychologically are able to receive information properly and to follow an appropriate education and training. Education on emergency response and disasters has not been implemented adequately in Indonesia, especially in Surakarta. Through this kind education and training, junior high school students are able to well cope with the emergency response procedures including fire emergency response, evacuation of flood disasters, first aid to victims of disasters, and determine the line of communication and make a proper coordination during the disaster situation with Badan Nasional Penanggulangan Bencana, Police, Hospitals and Fire Fighter.